Princípio da segurança jurídica no direito tributário: uma construção axiológica - Pereira, Luciano de Almeida (2009)
This work has the scope to demonstrate, through an interdisciplinary approach we call goal, the construction of the big principles of legal certainty, from a minimum of semantic meaning, complete with impressions Insite, so unique, each be cognoscente. For this, moot sciences as the Theory of Values, Semiotics, Semantics and others that support for the formation of such a concept of individual primacy. This, however, brings undeniable problems. We therefore identify them and discuss this issue